Dermoscopic Features of Pigmented Bowen Disease: A Multicenter Study on Behalf of the Ibero-Latin American College of Dermatology (CILAD) - Horacio Cabo; Gabriel Salerni; Emilia Cohen Sabban; Agustín Bollea Garlatti; Nicole Orendain; Sonia Rodriguez Saa; Renato Marchiori Bakos; Flavia Carolina Pozzobon; Virginia Mariana Gonzalez; Rosario Peralta; Cristian Navarrete-Dechent; Dominga Peirano; et al. (Mattioli1885, 2024)
Introduction: Studies focused on dermoscopic aspects of pigmented Bowen disease (pBD) in Latin American population are scarce and limited to only case reports or small series. Objectives: To report dermoscopic findings in a large series of 147 pBD diagnosed in Ibero-Latin American population. Methods: We conducted a multicentric, retrospective study on 147 histologically proven pBD under the auspices of the Dermoscopy Chapter of the Ibero-Latin American College of Dermatology. Results:  The study population consisted of 77 females (52%) and 70 males (48%) with a mean age of 68.6 years. 70.1% of patients had skin phototype 3, 15.6% to skin phototype 2, and 14.3% to skin phototype 4. On clinical examination, near 60% of pBD were flat, 70% presented with scales, and 90% were asymmetric. Under dermoscopy, structureless hypopigmented areas, dots brown and pink color were the most frequently observed. Regarding specific dermoscopic clues to pBD, the most prevalent were structureless hypopigmented areas, vessels arranged in linear fashion at the periphery, and pigmented lines or pigmented dots distributed in a linear fashion. Clustered, coiled, and dotted vessels were observed in 55.8%, 45.6%, and 45.6% of the cases, respectively. Conclusions: We report a large series of cases of pBD in Latin American patients, with most patients being skin phototype 3 and 4. Distinctively in our study, the pigmented structures and the clues derived from the presence of melanin were much more frequent than in previous reports in fair skin.